The interrelation of semantic structure and syntactic variation in Old English verb classes: catalogue of syntactico-semantic constructions - González Orta, Marta (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2005)
The aim of this paper is to motivate the syntactic and morphological behaviour of the Old English verbs which share the core meaning of 'to remember', 'to emit a smell', 'to produce a sound' and 'to speak' from their semantic structure. Firstly, as a result of the analysis of these verb subclasses, I will propose a subclass-based lexical template for each lexical subclass. Within the Lexical Grammar Model, lexical templates are conceived as lexical representations where meaning description is encapsulated and interacts with the syntactic behaviour of lexical units. In order to construct a lexical template, Role and Reference Grammar logical structures will be complemented by a semantic decomposition which will define different lexical (sub-)classes. Secondly, the Lexical Template Modelling Process will stipulate the linking between the syntactic and semantic representation of these verbs. This process will establish the lexical rules that account for the mapping between the different semantic constructions and the syntactic structures and alternations in which these verbs participate and the lexical templates codified by these verb subclasses. As a result, a catalogue of the syntactico-semantic constructions exhibited by these Old English verbal predicates will be provided.